Improving Packaging Logistics System: A Study Case of Camembert Cheese - Mushonnifun Faiz Sugihartanto; Syarifa Hanoum; Nalaputi Basoeki; Elif Tiryakioglu; Cynthia Ferrier (Direktorat Riset dan Pengabdian Kepada Masyarakat, 2021)
This research aims to assess the current packaging of Camembert cheeseusing the packaging evaluation method and propose suggestions to improvethe efficiency of packaging logistics that would impact the efficiency of theentire supply chain. We engage all supply chain actors in evaluating thepackaging features. The first packaging is not convenient as its weight andcost are pretty high for cheese. The secondary packaging is deemed lessefficient, whilst the tertiary packaging is not optimal in traceability. Speakingof cost, environmental impacts, especially impact on other features in thesupply chain, we propose solutions to replace the circular wooden box of thecheese with a cardboard box with a round shape. Then, only the cardboardtrays will be used as secondary packaging all along the supply chain. Thesecombined solutions reduce the handling work, the packaging material costand provide more convenience for all actors.